Assessing research misconduct in Iran: a perspective from Iranian medical faculty members - Shamsoddin, Erfan (BMC Med Ethics, 2021)
BACKGROUND: Research misconduct is a global concern in biomedical science. There are no comprehensive data regarding the perception and situation of scientific misconduct among the Iranian medical faculty members. We conducted a nationwide survey to assess the research misconduct among the medical faculty members in Iran. METHODS: We used the Persian version of the research misconduct questionnaire (PRMQ) on the Google Forms platform. We sent the survey link to a systematic random sample of medical faculty members in Iran (N = 4986). Descriptive analyses were performed on the individual items of the PRMQ, with frequencies and percentages for categorical and Likert-type response items, and means and standard deviation (S.D.) for continuous variables. Chi-square analysis was conducted to test hypotheses examining differences in the frequency of responses related to factors influencing misconduct. We also defined four tenure categories (TC) based on the working years of the participants as tenured faculty members. All the analyses were performed using R 3.6.0. RESULTS: The response rate was 13.8% (692 responses). Nearly 70% of the respondents agreed that their publication output would be of higher quality if there were no publication pressure. Approximately three-quarters (N =499, 72.1%) of the respondents had been aware of some instances of research misconduct during the previous year according to their understanding of misconduct. Among the participants, 18.5% perceived the effectiveness of their associated organisation’s rules for reducing research misconduct to be high or very high. Pressure for tenure was identified as the item most frequently perceived with a strong behavioural influence on engaging in research misconduct (80.2%). CONCLUSIONS: This study confirms that research misconduct needs to be actively addressed among the medical faculty members. Making policies with a focus on boosting awareness regarding the occasions of scientific misconduct and its management seems to be indispensable in the future in Iran. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12910-021-00642-2.